Aplicación de materiales de adsorción molecular en suelos francos, para su remediación ambiental en el barrio Anchiliví, cantón Salcedo, provincia de Cotopaxi, periodo 2022-2023. - Santamaría Santana, Andrea Estefanía (2023)
The current research work focused onto analyzing the soil quality after applying each the treatments for showing, which of them is the most effective in the remediation. In the first instance, it was made a biophysical diagnosis from Anchilivi neighborhood from Salcedo canton, where it was sought to determine the study area characteristics, immediately, it was analyzed if the different plots meet the soil quality adequate levels by comparing the got laboratory results, during the monitoring before and after applying each the treatments. As a last aim, it was calculated the efficacy each the used treatments in the different plots to finally determine which them is considered the most effective. To make the study, it proceeded by monitoring for 6 weeks in different experimental plots, in order to compare the 4 different compound treatments efficacy level based on zeolite and activated carbon, got data in the monitoring and through the laboratory analyzes were: it destined to the statistical graphs elaboration; into them, they were identified the high levels presence in each studied plot, by establishing in a general way that the levels do not comply, what is established in the reference values that harms the soil quality and the possible crops to develop in the sames; said work allowed to compare the adsorption levels generated starting of the different used substrates. The got information as a result the monitoring evidences, which the best treatments turns out to be number 2, made up of 15 kg of zeolite and 15 kg of activated carbon, because it has a 14.65% efficacy percentage.